Multicultural education in perspective Islamic educational science - Sholihah, Lilis; Kurniasih, Nia; Sahliah, Sahliah; Erihadiana, Mohamad (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
This research aims to examine multicultural education from the perspective of Islamic Education Science by identifying multicultural values in Islam and chlorinating challenges and obstacles in realizing multicultural education in the Islamic context. The research method used is qualitative with a library research approach. The results showed that multicultural education from an Islamic perspective is by integrating multicultural values into  Islamic religious learning and the focus is on developing attitudes and behaviors that respect cultural, religious, and ethnic diversity and of course by involving the development of character, knowledge, and attitudes by Islamic teachings. The challenges and obstacles in realizing multicultural education in the Islamic context are the difficulty of building a strong perception and awareness of the importance of multicultural education in Islamic societies, the existence of several traditions and cultures in Islamic societies emphasizing homogeneity, and resisting change or outside influences. Finally, the development of curricula and teaching methods that conform to multicultural principles in the Islamic context requires profound adjustment. Penelitian ini bertujuan mengkaji secara mendalam tentang  pendidikan multikultural dari perspektif Ilmu Pendidikan Islam dengan mengidentifikasi nilai –nilai multicultural dalam Islam dan mengeklorasi tantangan dan hambatan dalam mewujudkan pendidikan multicultural dalam konteks Islam.  Metode penelitian yang digunakan adalah kualitatif dengan pendekatan library research. Hasil penelitian menunjukkan bahwa pendidikan multikultural dalam  persfektif Islam yaitu dengan mengintegrasikan nilai-nilai multikultural dalam pembelajaran agama Islam dan fokusnya adalah pada pengembangan sikap dan perilaku yang menghargai keragaman budaya, agama, dan etnis dan tentunya dengan melibatkan pengembangan karakter , pengetahuan, dan sikap yang sesuai dengan ajaran Islam. Adapun yang menjadi tantangan dan hambatan dalam mewujudkan pendidikan multicultural dalam kontek Islam adalah sulitnya membangun persepsi dan kesadaran yang kuat tentang pentingnya pendidikan multikultural dalam masyarakat Islam,adanya beberapa tradisi dan budaya dalam masyarakat Islam menekankan pada homogenitas dan menolak perubahan atau pengaruh luar. Dan terkahir pengembangan kurikulum dan metode pengajaran yang sesuai dengan prinsip-prinsip multikultural dalam konteks Islam memerlukan penyesuaian yang mendalam.